2005
DOI: 10.1063/1.1850897
|View full text |Cite
|
Sign up to set email alerts
|

Parallel temperatures in supersonic beams: Ultracooling of light atoms seeded in a heavier carrier gas

Abstract: Supersonic expansion is a very powerful tool to produce an atomic beam with a well defined velocity and, by seeding a test gas in such an expansion, the energy of the test gas can be transferred, at least partially, to the very-low-temperature carrier gas. The case usually studied is the one of a heavy gas seeded in a light carrier gas and, in this case, the parallel temperature of the seeded gas is always larger than the one of the carrier gas. In the present paper, we study the opposite case which has receiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…The main limitation on the present measurement of the electric polarisability of lithium 7 Li comes from the uncertainty on the most probable atom velocity u. With some exceptions, like the Aharonov-Casher phase shift [18] which is independent of the atom velocity, a phaseshift induced by a perturbation is inversely proportional to the atom velocity, at least when a static perturbation is applied on one interfering beam.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The main limitation on the present measurement of the electric polarisability of lithium 7 Li comes from the uncertainty on the most probable atom velocity u. With some exceptions, like the Aharonov-Casher phase shift [18] which is independent of the atom velocity, a phaseshift induced by a perturbation is inversely proportional to the atom velocity, at least when a static perturbation is applied on one interfering beam.…”
Section: Discussionmentioning
confidence: 99%
“…We have made a measurement of the electric polarizability of lithium atom 7 Li by atom interferometry and we have obtained α = (24.33 ± 0.16) × 10 −30 m 3 = 164.19 ± 1.08 a.u. with a 0.66% uncertainty.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This effect has been demonstrated for various seed species, including large organic molecules [198]. For light species seeded in a heavier carrier gas, it has been found that the translational temperature of the seed can even be lower than that of the carrier [199]. As discussed before, the cooling of the seed is limited by condensation in the gas jet.…”
Section: Seeded Gas Jetsmentioning
confidence: 94%